Why mouse oocytes and early embryos ignore miRNAs? - Svoboda, Petr (RNA biology, 2010)
Small RNA molecules regulating gene expression received a status of omnipresent master regulators of eukaryotic lives with almost supernatural powers. Mammals hold at least three mechanisms employing small RNA molecules for regulating gene expression. One of these mechanisms, the microRNA (miRNA) pathway, involves currently over a thousand of genome-encoded different miRNAs that are claimed to extend their control over more than a half of a genome. Here, I discuss how and why mouse oocytes and early embryos ignore the regulatory power of miRNAs, adding another surprising feature to the field of small RNAs.
Keywords: embryo savčí; Mice; oocyty; RNA Interference; Gene Expression Regulation, Developmental; RNA, Messenger, Stored; mikro RNA; vývojová regulace genové exprese; Animals; Oocytes; RNA interference; zvířata; RNA messenger skladovaná; myši; MicroRNAs; Embryo, Mammalian